Formulation and Nutritional Evaluation of Mango Seed Kernel-Coffee Flavoured Multi-Purpose Flour - Mustafa Kamal, Nur Athirah; Zalilah Murni Yunus, (Enhanced Knowledge in Sciences and Technology, 2024)
Mango Seed Kernel Coffee (MSKC) is a tropical fruit with antioxidant properties, moisture content, and pH value. It is used to create MSKC Flavoured Multi-Purpose Flour from mango seed kernel and spent ground coffee waste. The study used various methods to analyze the properties of raw materials and finished product. Mango seed kernel and spent ground coffee generate high waste in the food industry, causing environmental pollution and economic losses. Mango seeds kernel and spent ground coffee can be transformed into a new product, reducing waste and providing health benefits. This study aims to formulate Mango Seed Kernel Coffee (MSKC) flavoured multi-purpose flour to help people with gluten intolerance, reduce gluten consumption, and promote healthier eating habits. The research objectives is to to characterize physicochemical properties of Mango Seed Kernel Coffee (MSKC) in term of antioxidant content, moisture content, and pH value, to formulate MSKC Flavoured Multi-Purpose Flour from mango seed kernel and spent ground coffee waste using 3 formulations for gluten intolerance and to characterize the multipurpose flour in term of water holding capacity, antioxidant content, moisture content and bulk density. This study collected data on the physicochemical properties of raw materials, including antioxidant content, moisture content, and pH value. It also analyzed MSKC in terms of antioxidant content, moisture content, water-holding capacity, and bulk density. Results showed high antioxidant content but low moisture content, with a slightly acidic pH value. All 12 formulations were analyzed, with formulation 1 having the highest antioxidant content and formulation 3 having the lowest moisture content. The water holding capacity range was between 15.5333 ± 1.52753ᵃ and 24.2000 ± 2.00000ᶜ, with formulation 8 having the highest bulk density reading.